Femoral component retention in Rorabeck type III periprosthetic knee fracture with plating fixation and bone cement augmentation. A new surgical technique and four cases reported - Alfonso Queipo-de-Llano; Jorge Mariscal Lara; Antonio Leiva Gea; Borja Delgado-Rufino (Trauma Case Reports)
Although dual implant constructs have recently been explored with promising results in very distal periprosthetic femur fractures (PPKF), the gold standard treatment of Rorabeck and Taylor type III PPKF remains a distal femur replacement or a highly constrained rotating hinge implant. However, this surgery is very aggressive and expensive for functionally low-demanding elderly patients. A new surgical technique using locking plates with polymethyl methacrylate cement augmentation is described to retain the femoral component avoiding its replacement. Four patients were treated and followed up for more than one year postoperative without any complications, their femoral component was retained without any loosening and the mobility in the Barthel Index remained unchanged.